The decline in carving African and Asian elephant tusks in Nepal and the decrease in ivory items for retail sale in Kathmandu - Martin, Esmond; Martin, Chryssee; Vigne, Lucy (Pachyderm, 2013)
The Nepal ivory industry has collapsed since early 2001, when the last survey was conducted. The few remaining craftsmen have stopped carving ivory. The number of shops selling ivory items has fallen from 57 in February 2001 to 19 in December 2012. During this period ivory items on display for sale in Kathmandu dropped from 1,546 to 208. Smuggled raw ivory from Africa and Asia used to come into Nepal via India, but both the India and the Nepal governments have improved their border controls. Wildlife law enforcement in Nepal has strengthened considerably since 2010 with the establishment of government committees and bureaus dealing with wildlife crime all over the country. All ivory is illegal to sell or to display in shops, and vendors are now reluctant to sell new ivory items and are trying to offload their last remaining ivory objects. Turnover is slow as customer demand has fallen, partly as Nepalese now prefer to buy gold items and also because foreign tourists (the main buyers) show little interest in buying ivory as the selection is poor and there is a greater risk entailed in smuggling worked ivory out of the country. Thus Nepal is not a threat to Africa’s or Asia’s elephants. L’industrie de l’ivoire du Népal s’est effondrée depuis le début de 2001, lorsque la dernière étude a été réalisée. Les quelques artisans restants ont cessé de sculpter l’ivoire. Le nombre de magasins vendant des articles en ivoire a chuté de 57 en février 2001 à 19 en décembre 2012. Pendant cette période, les objets en ivoire exposés pour la vente à Katmandou ont chuté de 1546 à 208. La contrebande de l’ivoire brut d’Afrique et d’Asie venait d’habitude au Népal via l’Inde, mais les gouvernements du Népal et de l’Inde ont amélioré leurs contrôles aux frontières. L’application de la loi de la faune au Népal s’est considérablement renforcée depuis 2010 avec la création des comités et bureaux gouvernementaux traitant de la criminalité de la faune dans tout le pays. Toute vente ou exposition de l’ivoire dans les magasins est illégale, et les vendeurs sont maintenant réticents à vendre des articles en ivoire et essaient de se débarrasser de leurs derniers objets d’ivoire restants. La rotation est lente car la demande des clients a diminué. D’abord, les Népalais préfèrent maintenant acheter des objets en or et aussi les touristes étrangers (les principaux acheteurs) montrent peu d’intérêt pour l’achat d’ivoire dont la sélection est limitée et il y a un risque de transporter l’ivoire travaillé à l’extérieur du pays. Ainsi Népal n’est pas une menace pour les éléphants d’Afrique ou d’Asie.